Graded Association Between Kidney Function and Impaired Orthostatic Blood Pressure Stabilization in Older Adults. Issue 5 (May 2017) - Canney, Mark; O'Connell, Matthew D. L.; Sexton, Donal J.; O'Leary, Neil; Kenny, Rose Anne; Little, Mark A.; O'Seaghdha, Conall M.
Abstract : Background: Impaired orthostatic blood pressure (BP) stabilization is highly prevalent in older adults and is a predictor of end‐organ injury, falls, and mortality. We sought to characterize the relationship between postural BP responses and the kidney. Methods and Results: We performed a cross‐sectional analysis of 4204 participants from The Irish Longitudinal Study on Ageing, a national cohort of community‐dwelling adults aged ≥50 years. Beat‐to‐beat systolic and diastolic BP were measured during a 2‐minute active stand test. The primary predictor was cystatin C estimated glomerular filtration rate (eGFR) categorized as follows (mL/min per 1.73 m 2 ): ≥90 (reference, n=1414); 75 to 89 (n=1379); 60 to 74 (n=942); 45 to 59 (n=337); <45 (n=132). We examined the association between eGFR categories and (1) sustained orthostatic hypotension, defined as a BP drop exceeding consensus thresholds (systolic BP drop ≥20 mm Hg±diastolic BP drop ≥10 mm Hg) at each 10‐second interval from 60 to 110 seconds inclusive; (2) pattern of BP stabilization, characterized as the difference from baseline in mean systolic BP/diastolic BP at 10‐second intervals. The mean age of subjects was 61.6 years; 47% of subjects were male, and the median eGFR was 82 mL/min per 1.73 m 2 . After multivariable adjustment, participants with eGFR <60 mL/min per 1.73 m 2 were approximately twice as likely to have sustained orthostatic hypotension ( P =0.008 for trend across eGFR categories). We observed a graded association between eGFR categories and impaired orthostatic BP stabilization, particularly within the first minute of standing. Conclusions: We report a novel, graded relationship between diminished eGFR and impaired orthostatic BP stabilization. Mapping the postural BP response merits further study in kidney disease as a potential means of identifying those at risk of hypotension‐related events.